Classification of hydrogeological structure along the Red river in the Hanoi area - Trieu, Duc Huy; Tong, Ngoc Thanh; Nguyen, Van Lam; Pham, Ba Quyen; Hoang, Dai Phuc; Trinh, Hoai Thu (Vietnam Journal of Marine Science and Technology, 2021)
Hanoi city has abundant groundwater, supplemented by the surface water (mainly Red River) all year round, and the extensive shallow aquifers, which are easily exploited by large-diameter wells. There always exists some open hydrogeological windows in the Red River area with an open structure; therefore, the groundwater has a strained hydraulic relationship with the Red River water system Along the Red River from Ba Vi to the end of Phu Xuyen district, there are nine regions with three types and four sub-types of different hydrogeological structures. In particular, the sub-type I-A of the groundwater has a tight hydraulic correlation with the Red River since the hydrogeological structure of the Red River bottom includes three aquifers: Holocene (qh), upper Pleistocene (qp2), and lower Pleistocene (qp1) that constructs a hydraulic system. The sub-type I-B is characterized by the hydrogeological structure at the Red River bottom, including the aquitard in Vinh Phuc and two aquifers qp2 and qp1, which form a hydraulic system. The sub-type II-A is distinguished by the fact that the Red River crosses the aquifer qh; there are no aquitards between the aquifer qh and qp2 to form a hydraulic system; the aquitard separates the aquifer qp1. The sub-type II-B is identified by the fact that the Red River crossing the aquifer qh; there is an aquitard between the aquifer qh and qp2; there are no aquitards between the aquifer qp2 and qp1 so that can create a hydraulic system. Type III has a solid existence of both aquifers and aquitards; thus, the hydraulic relationship between the Red River and the aquifers qp2 versus qp1 is inferior.